Recurrent Wheezing In Preschool Children; The Associated Factors. A Cross Sectional Study In Tertiary Care Hospital - Mumtaz, Shaista; Farooq Ikram; Sarah Javed; Asbah Rahman; Ammara Jamil; Atif Naseem Abbasi (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine associated factors in preschool children presenting with recurrent wheezing to children out patient department.Study Design: Cross sectional study.Place and Duration of Study: Pediatrics department, Pak Emirates Military Hospital Rawalpindi from April 2019 to January 2021.Methodology: 300 children with age 2-5 year presenting with recurrent wheezing to children outpatient department were included in the study. Vitamin D levels were carried out in all of them and levels of